EDUCAÇÃO ESPECIAL E INCLUSIVA NA EDUCAÇÃO INFANTIL: PESQUISA BIBLIOGRÁFICA - PATRICIA SANTOS DE OLIVEIRA (2024)
Early Childhood Education, the first stage of basic education, aims for the integral development of children up to 5 years old. In Early Childhood Education, learning must occur through experiences, with interactions and play as foundational axes for all children. Based on this, the question was raised: what are the challenges and advancements in Early Childhood Education for Special Education? Thus, the objective of the research that resulted in this text is to discuss the importance of Inclusive Education in Early Childhood Education and the specific aim of understanding the advancements and challenges of Special Education from an inclusive perspective in Early Childhood Education. The methodology used consisted of bibliographic research at the Coordination for the Improvement of Higher Education Personnel (Capes), the Scientific Electronic Library Online (SciELO), and the Institutional Repository of the Federal University of Mato Grosso do Sul (UFMS), specifically from the Pantanal Campus (CPan), using the following descriptors: "Inclusive Education and Early Childhood Education"; "Target Audience of Special Education and Early Childhood Education," and "Special Education and Early Childhood Education". From this, texts published in the last five years, specifically from 2018 to 2023, were selected, corresponding to the year of implementation of the National Common Curricular Base and the year prior to the beginning of the research. The texts were analyzed based on inspiration from Bardin's Content Analysis. Thus, it was possible to understand that, despite legislative and pedagogical advancements, there are still challenges that need to be overcome to ensure special and inclusive education in Early Childhood Education. Inclusion is not just about integrating learners with specific needs but about providing an educational environment that values and respects diversity, promoting the integral development of all children.